Single cell analysis revealed that two distinct, unique CD4+ T cell subsets were increased in the small intestinal intraepithelial lymphocytes of aged mice - Yonemoto, Yuki; Nemoto, Yasuhiro; Morikawa, Ryo; Shibayama, Nana; Oshima, Shigeru; Nagaishi, Takashi; Mizutani, Tomohiro; Ito, Go; Fujii, Satoru; Okamoto, Ryuichi (Frontiers in Immunology, 2024)
Recent advances in research suggest that aging has a controllable chronic inflammatory disease aspect. Aging systemic T cells, which secrete pro-inflammatory factors, affect surrounding somatic cells, and accelerate the aging process through chronic inflammation, have attracted attention as potential therapeutic targets in aging. On the other hand, there are few reports on the aging of the intestinal immune system, which differs from the systemic immune system in many ways. In the current study, we investigated the age-related changes in the intestinal immune system, particularly in T cells. The most significant changes were observed in the CD4+ T cells in the small intestinal IEL, with a marked increase in this fraction in old mice and reduced expression of CD27 and CD28, which are characteristic of aging systemic T cells. The proliferative capacity of aging IEL CD4+ T cells was significantly more reduced than that of aging systemic T cells. Transcriptome analysis showed that the expression of inflammatory cytokines was not upregulated, whereas Cd8α, NK receptors, and Grazymes were upregulated in aging IEL CD4+ T cells. Functional analysis showed that aging IEL T cells had a higher cytotoxic function against intestinal tumor organoids in vitro than young IEL T cells. scRNAseq revealed that splenic T cells show a transition from naïve to memory T cells, whereas intestinal T cells show the emergence of a CD8α+CD4+ T cell fraction in aged mice, which is rarely seen in young cells. Further analysis of the aging IEL CD4+ T cells showed that two unique subsets are increased that are distinct from the systemic CD4+ T cells. Subset 1 has a pro-inflammatory component, with expression of IFNγ and upregulation of NFkB signaling pathways. Subset 2 does not express IFNγ, but upregulates inhibitory molecules and nIEL markers. Expression of granzymes and CD8α was common to both. These fractions were in opposite positions in the clustering by UMAP and had different TCR repertoires. They may be involved in the suppression of intestinal aging and longevity through anti-tumor immunity, elimination of senescent cells and stressed cells in the aging environment. This finding could be a breakthrough in aging research.